The Expansion And Equitable Access To Early Childhood Education In The City Of Baubau - Asma Kurniati; Suardin Suardin (Universitas of Muhammadiyah Makassar, 2022)
This study aims to determine the impact of implementing Baubau Mayor Regulation Number: 1 of 2014 regarding equitable access to early childhood education. In this research, the method used is descriptive qualitative evaluation, that is, research in which one of them describes or takes pictures of policy implementation. The results of the study indicate that the Mayor of Baubau Regulation Number 81 of 2014 concerning the Implementation of Early Childhood Education in the city of Baubau is a policy that has been carried out for a long time and has an impact on increasing and equalizing the number of units, teachers, students as a form of community participation in PAUD services. There are also supporting and inhibiting factors that use a reference in improving the rearrangement of the policy.Penelitian ini mendeskripsikan dampak implementasi Peraturan Walikota Baubau Nomor:81 Tahun 2014 terkait pemerataan akses pendidikan anak usia dini. Metode yang digunakan adalah evaluasi bersifat kualitatif deskriptif, yaitu penelitian yang salah satunya menggambarkan atau memotret tentang implemenetasi kebijakan. Hasil penelitian menunjukkan bahwa Peraturan Walikota Baubau Nomor 81 Tahun 2014 tentang Penyelenggaraan Pendidikan Anak Usia Dini di kota Baubau merupakan kebijakan yang telah lama dilakukan dan berdampak pada peningkatan dan pemerataan pada jumlah satuan, guru, peserta didik sebagai wujud partisipasi masyarakat pada pelayanan PAUD. Terdapat pula faktor-faktor pendukung dan penghambat yang dapat dijadikan sebagai acuan dalam perbaikan penyusunan kembali kebijakan tersebut.